Applicability of bolton's analysis to a South Telangana population - T Saritha; C Sunitha; P Kiran Kumar; R Naveen (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the study was to assess the anterior and overall tooth size discrepancies in different malocclusions and evaluate its effect on gender in a sample of South Telangana (Khammam) population and to compare it with Bolton standards. Materials and Methods: The study sample consisted of 311 pretreatment study casts, which were selected from records of orthodontic patients, who were residents of Khammam, South Telangana. The sample was divided into three groups based on Angle Class I, II, and III malocclusions and further subdivided into male and female groups. The mesiodistal diameters of the teeth were measured using digital calipers, and the Bolton's analysis was carried out. Statistical Analysis Used: Intraclass correlation coefficient was assessed using Dahlberg's formula. ANOVA and post hoc least significant difference test were used. Results: The mean anterior and overall ratios were 79.17 ± 2.91 and 92.3 ± 1.88, respectively. A total of 64% and 45% of the study population had tooth size discrepancies in the anterior and overall ratios when assessed for >±1 standard deviation (SD). When the sample was assessed for discrepancies >±2 SD, it was observed that a total of 33.8% and 5.5% patients had anterior and overall tooth size discrepancies. Conclusions: With significant differences being observed between Bolton's and the present study values, the need for population standards gains importance for better results at the end of orthodontic treatment.